The Challenge of Modernisation : Education and Adult Education Policy in Hungary, 1950 to the Present - Pethö, Lazlo [Verfasser] (My University, 2000)
In: The Rise and Fall of Adult Education Institutions and Social Movements. The Proceedings of the Seventh International Conference on the History of Adult Education. - (2000) , S. 61-73
Keywords: L 4.2.2 Klassisches Fernlernen; L 4.2.3 Internetbasiertes Lernen / E-Learning; I 2.2.2 Osteuropa; Erwachsenenbildung; Zeitgeschichte; Sozialer Wandel; Berufliche Weiterbildung; Fernunterricht; Weiterbildungspolitik; Ungarn